A rise in births following contraceptive failure in France between 2010 and 2016: results from the French national perinatal surveys - Camille Bonnet; Béatrice Blondel; Caroline Moreau (BMC, 2021)
Abstract Background In France, while the prevalence of contraception is high, a significant proportion of pregnancies are unintended. Following the 2012 pill scare, the contraceptive method mix, which was mostly comprised of pills and intrauterine devices (IUD), has become more diversified. In this changing landscape, our objective was to describe trends in live births resulting from contraceptive failure and evaluate how patterns of contraceptive use have contributed to observed changes between 2010 and 2016. Methods We used data from the 2010 and the 2016 French National Perinatal surveys which included all births from all maternity units in France over a one-week period. Interviews collecting information about pre-conception contraceptive practices were conducted in the maternity ward post-delivery. Women were classified as having a contraceptive failure if they discontinued contraception because they were pregnant. Our study sample included adult women who had a live birth, had ever used contraception and did not undergo infertility treatment (n = 11,590 in 2010 and n = 9703 in 2016). We evaluated changes in contraceptive failure over time using multivariate Poisson regressions to adjust for sociodemographic characteristics and pre-pregnancy contraceptive methods. Results Pre-pregnancy contraception evolved between 2010 and 2016 with a 12.3% point-drop in pill use, and conversely, 4.6%- and 3.2%-point increases in IUD and condom use, respectively. Use of other barrier or natural methods doubled between 2010 and 2016 but remained marginal (1.4% in 2010 vs 3.6% in 2016). Between 2010 and 2016, the proportion of live births resulting from contraceptive failure rose from 7.8 to 10.0%, with higher risks among younger, parous and socially disadvantaged mothers. The risk ratio of contraceptive failure in 2016 compared to 2010 remained higher after sociodemographic adjustments (aRR = 1.34; 95% CI; 1.23-1.47) and after adjusting for pre-pregnancy contraceptive method mix (aRR = 1.35; 95% CI; 1.25-1.49). Increases in contraceptive failures were concentrated among pill and condom users. Conclusions Recent shifts in contraceptive behaviors in France following the 2012 pill scare may be associated with a subsequent increase in births resulting from short acting contraceptives failures.